Пошаговое объяснение:
№1
{х/5 + у/3 = 1 | * 15
{х/4 - у/2 = 1 | * 4
{3х + 5у = 15
{х - 2у = 4
{3х + 5у = 15
{х = 4 + 2у
1)
3х + 5у = 15
3(4 + 2у) = 15
12 + 6у = 15
6у = 15 - 12
6у = 3
у = 3 : 6
у = 0,5
2)
х = 4 + 2у
х = 4 + 2 * 0,5
х = 4 + 1
х = 5
(5; 0,5)
№2
{х/2 + у/5 = 2 | * 20
{х/3 + у/2 = 1 | * -30
{10х + 4у = 40
{-10х - 15у = -30
{-11у = 10
{10х + 4у = 40
1)
-11у = 10
у = 10 : (-11)
у = -10/11
2)
10х + 4у = 40
10х + 4 * (-10/11) = 40
10х - 40/11 = 40
10х = 40 + 40/11
10х = 480/11
х = 480/11 : 10
х = 480/11 * 1/10
х = 48/11
(48/11; -10/11)